{Cloud, IoT}-powered smart weather station for microclimate monitoring - Mohamed Fazil Mohamed Firdhous; B H Sudantha (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Microclimate monitoring is important in many practical situations involving agriculture, archaeology and other environments. Microclimate is defined as the environmental conditions that differs from that of surrounding areas. In certain situations, these different conditions are artificially generated for creating a conducive environment for achieving better results. Environments such as greenhouses and climate controlled beehives require to maintain their environments within close variations for optimum results. Similarly archaeological sites including show caves, frescos and parks get disturbed easily by the changes in their immediate environments. Hence monitoring and managing these environments is a must for the proper maintenance of them. In this paper, the authors present an IoT enabled microclimate monitoring weather station that can be installed anywhere and monitor the required parameters from remotely. The modular design enables the station to be easily modified to suit any environment. The weather station collects and transmit data at fixed intervals to the cloud powered processing system over the mobile communication network . The sensors have been calibrated using the standard calibration methods using conventional devices as references. The results obtained from the prototype shows that the weather station works satisfactorily reading the real environment conditions.